ENSURING THE SECURITY OF QUANTUM SYSTEMS: ALGORITHMS AND METHODS - Saidakhmedov Eldor Islomovich; Qahhorova Nargiza Xayit qizi; Toshtemirova Sarvara To’lqin qizi (Web of Journals Publishing, 2025)
This article reviews the main algorithms and methods aimed at ensuring the security of quantum systems. The article provides detailed information about important technologies such as quantum cryptography, post-quantum cryptography, and quantum error correction. Algorithms such as Quantum Key Distribution (QKD), Lattice-based cryptography, Hash-based signatures, and Surface Codes are used to ensure the security of quantum systems. These algorithms ensure the confidentiality, integrity, and availability of information. The article covers the latest achievements in the field of quantum system security and emphasizes the importance of research and development in this area. Along with the development of quantum technologies, algorithms for ensuring their security are also constantly being improved. This article is a useful resource for those interested in the fields of information security, cryptography, and quantum computing.
Keywords: Quantum systems, quantum security, quantum encryption (Quantum Cryptography), quantum key distribution (QKD), post-quantum cryptography (Post-Quantum Cryptography), Lattice-based cryptography, Hash-based signatures, quantum error correction (Quantum Error Correction), Surface Codes, Cryptographic algorithms, Information security.